The Unmet Needs of Hepatitis E Virus Diagnosis in Suspected Drug-Induced Liver Injury in Limited Resource Setting - El-Mokhtar, Mohamed A.; Ramadan, Haidi Karam-Allah; Thabet, Marwa M.; Abd-Elkader, Alaa S.; Fouad, Magdy; Sallam, Mohammad M.; Elgohary, Elsayed A.; Abd El-Hafeez, Amer Ali; Mohamed, Mona Embarek; Sayed, Ibrahim M. (Frontiers in Microbiology, 2021)
Background: Currently, there is no specific biomarkers for drug-induced liver injury (DILI), and the diagnosis of DILI is based mainly on the exclusion of other causes of liver dysfunction and the recognition of potential causative drugs. Hepatitis E virus (HEV) diagnosis is not routinely enrolled in many countries and HEV infection could be misdiagnosed as DILI. Methodology: We retrospectively analyzed plasma samples (n=80) collected from suspected DILI for HEV markers such as anti-HEV IgM, anti-HEV IgG, and HEV RNA. Anti-HEV antibodies were assessed using commercial ELISA kits. HEV RNA was tested by RT-qPCR targeting HEV ORF2/3 and the receiver operating characteristic (ROC) curve was plotted, a putative threshold for liver function parameters was determined. Results: Out of 80 samples, 12 samples were positive for anti-HEV IgM and anti-HEV IgG, and HEV RNA was detected in 7 samples. The median viral load was 3.46 x103IU/ml, and the isolated viruses belonged to HEV genotype 1. The level of liver enzymes such as alanine transaminase (ALT) and aspartate transaminase (AST), but not alkaline phosphatase (ALP) was significantly higher in HEV confirmed cases than non-HEV confirmed cases. We identified a plasma ALT of at least 415.5 IU/l, AST at least 332 IU/ml, or ALT/ALP ratio of at least 5.08 could be used as a guide for the patients diagnosed as DILI to be tested for HEV infection. The previous liver function parameters showed high sensitivity, and good specificity. Conclusion: HEV was detected in suspected DILI cases. The diagnosis of DILI is not secure until HEV testing is done. Liver function parameters can be used as a guide for HEV testing in suspected DILI cases in limited resources countries. Keywords: HEV; DILI; acute hepatitis; liver function tests; HEV screening; limited resource settings.